APLIKASI PUPUK HAYATI VP3 DIBANDINGKAN DENGAN EMPAT MACAM PUPUK HAYATI YANG BEREDAR DIPASARAN TERHADAP HASIL KACANG HIJAU (Vigna radiata L.) DI LAPANG - rosita dwi (AGRONISMA, 2020)
ABSTRACTThe aims of this research is to determine the effect of application of VP3 biofertilizer compared with biofertilizers circulating in the market on the results of mungbean in field. The research was conducted on land in Bumi Asri Housing, Dau District, Malang Regency, and the Applied Laboratory, Faculty of Agriculture, Malang Islamic University from June to October 2019. The research used a Randomized Block Design (RBD) with 6 treatments and was repeated 3 times. The results showed that the treatment of VP3 biofertilizer when compared with biofertilizers circulating in the market in general gave better results to the growth and yield variables of mungbean in field. This was seen to be especially significant on the growth variable the number of root nodules, and on variable total seeds weight per plot. However, the content of the NPK elements of soil treatment of VP3 biofertilizer and biofertilizers circulating in the market shows the same results, namely the N element in the soil is low, while the P and K elements are high.